The Effectiveness of Using Dubbing and Subtitle Methods on Mastering Arabic Vocabulary for Class XI MAN 1 Ponorogo Students | Efektivitas Penggunaan Metode Dubbing dan Subtitle Terhadap Penguasaan Kosakata Bahasa Arab Siswa Kelas XI MAN 1 Ponorogo - Nurul izzah amir; Anis Mahmudah; Fatikha Azzatunnuriyah; Iklima Dwi Pahlevi (ATHLA : Journal of Arabic Teaching, Linguistic and Literature, 2023)
This research is to find out the effectiveness of using dubbing and subtitle methods on Arabic vocabulary. The purpose of this research was to determine students' Arabic vocabulary before and after the dubbing and subtitle methods were applied. The research method used is a quasi-experiment with a one-group pre-test post-test design. The sample of this research was 72 students of class XI MAN 1 Ponorogo. Based on the results of data analysis before being given treatment, the average value of students was 45.76 while after being given treatment was 77.01. This means that there is an increase of 31.25. In the Wilcoxon test, a significance level/p value of 0.001 is obtained, if the Asymp.Sig. (2-tailed) smaller than < 0.05 then Ha is accepted. This shows that there is a significant difference between the pretest scores and posttest scores. This means that there are differences in Arabic vocabulary mastery of class XI MAN 1 Ponorogo students before and after using the dubbing and subtitle method.